Little book worm: early learning exposure - Abd Jalil, Norazlina; Mohd Yatim, Melissa De Valda; Husien, Hadirah; Zainal, Nur Adnin Fazliyana; Nordin, Siti Khairiyah (Universiti Teknologi MARA, Kedah, 2019)
The adoption of the right to access information or freedom of information is an essential element for every citizen to create a learning environment. Library is the only place in community which provides various sources of information that will help to improve their education, develop new skills, find jobs, build businesses, make informed agricultural and health decisions or gain insights into environmental issues. The unique roles of library is important for healthy development of the society and also providing access to information in all formats by delivering services and programs that meet the needs of current trends in information revolution. This project has focused on toddlers to pre-schoolers to support their early literacy exposure by using easy platform. Early literacy exposures are important as they will be able to increase their vocabulary and nurture good communication skill to communicate with others. This mobile-application will comprise several different features such as the brief introduction of Jawi alphabet, numbers, alphabets, colours and will be equipped with songs that are related to the early learning such as alphabets song and others in one single platform. This features attract the toddlers and also pre-schoolers users as music helps young children build powerful thought networks that fortify their learning in areas as varied as language processing, visual perception, memory, mathematics, and, of course, creative expression. Early education that conducted using the mobile-application also has advantage such as education can be conducted at all time without having any constrain as it can be access whenever needed. Furthermore, this mobile-application also will be designed with interface that is user friendly for all of its users. This project also can be used to fill the gap between generations as learning using the mobile-application is not uncommon as this generation are more to the digital literacy.